2010
DOI: 10.1071/hc10234
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist perceptions of clinical medication reviews

Abstract: INTRODUCTION: Changes in delivery of health care services has led to pressure for community pharmacists to extend their traditional role and become more involved with patient-focussed services such as medication reviews, in collaboration with general practitioners (GPs). This has not been generally implemented into routine practice, and many barriers have been suggested that inhibit community pharmacists extending their role. These have often focussed on physical or functional barriers. This study explores pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Seven articles on clinical medication reviews described 4 different interventions . Three of the articles addressed government‐funded Home Medicines Reviews (HMRs) in Australia and reported studies on 2 approaches to HMRs In the other HMR intervention, community pharmacists interviewed patients to obtain a comprehensive medication profile and, after conducting a review, wrote a report on the HMR findings and recommendations to the GP .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles on clinical medication reviews described 4 different interventions . Three of the articles addressed government‐funded Home Medicines Reviews (HMRs) in Australia and reported studies on 2 approaches to HMRs In the other HMR intervention, community pharmacists interviewed patients to obtain a comprehensive medication profile and, after conducting a review, wrote a report on the HMR findings and recommendations to the GP .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were not RCTs (intervention studies (n=2), document analyses (n=4), qualitative interviews (n=2), a process description (n=1), a cohort study (n=1), combination of qualitative interviews and a survey). Regardless of community pharmacist contributions to medication review interventions or comprehensiveness of medication review comprehensiveness, interventions led to a reduction in actual or potential DRPs (n=6), better adherence (n=3), and use of fewer medicines (n=2) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fact of perceiving collaboration as useful not only influences the willingness to initiate collaboration, but also its continuity (Bryant et al, 2010b). Various studies have indicated that health professionals who collaborate wish to continue doing so as they feel more comfortable in the interaction, communication improves (Dieleman et al, 2004) and an improvement in results is perceived (Laubscher et al, 2009;Teinilä et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10][11][12][13][14][15][16] Previous work had primarily focused on service characteristics, [17][18][19] factors associated with service adoption, 13,16,20,21 barriers and facilitators of implementation, 12,22,23 pharmacy culture considerations, 24 and stakeholder perceptions of various services. 25,26 Implementation strategies, or the methods, techniques, and/or activities used to integrate a clinical intervention or patient care service into usual care systematically and purposefully, are a critical area for future scholarly work focused on community pharmacy practice. 27,28 The pharmacy literature suggests that training and compensation have been the most utilized strategies in driving implementation efforts.…”
mentioning
confidence: 99%